Foundations of sports coaching - Robinson, Paul E (Routledge, Taylor & Francis Group, 2015)
Now in a fully revised and updated second edition, Foundations of Sports Coaching is a comprehensive and engaging introduction to the practical, vocational and scientific principles that underpin the sports coaching process. It provides the reader with all the skills, knowledge and scientific background they will need to prepare athletes and sports people technically, tactically, physically and mentally. With practical coaching tips, techniques and tactics highlighted throughout, the book covers all the key components of a foundation course in sports coaching,